The role of exosomal PD-L1 in tumor progression and immunotherapy - Xie, Feiting (Mol Cancer, 2019)
Programmed death ligand 1 (PD-L1), a type I transmembrane protein, binds to its receptor PD-1 to suppress the activation of T cells, thereby maintaining immunological homeostasis. In contrast, tumor cells highly express PD-L1, which binds to receptor PD-1 expressed on activated T cells, leading to immune escape. Anti-PD-1/PD-L1 immune checkpoint therapy blocks the binding of PD-1/PD-L1 to reinvigorate the exhausted T cells, thereby inhibiting tumor growth. Exosomes are biologically active lipid-bilayer nanovesicles secreted by various cell types that mediate intercellular signal communication. Numerous studies have shown that tumor cells are able to promote tumor epithelial-mesenchymal transition, angiogenesis, and immune escape by releasing exosomes. Recent studies imply that tumor-derived exosomes could carry PD-L1 in the same membrane topology as the cell surface, thereby resisting immune checkpoint therapy. In this review, we mainly discuss the role of exosomes in the regulation of tumor progression and the potential resistance mechanism to immunotherapy via exosomal PD-L1. In addition, we propose that exosomal PD-L1 may have the potential to be a target to overcome resistance to anti-PD-1/PD-L1 antibody therapy.